2013
DOI: 10.1136/oemed-2013-101717.36
|View full text |Cite
|
Sign up to set email alerts
|

36 Occupational health services for small-scale industry workers in a district of Sri Lanka

Abstract: Objectives To describe the provision of occupational health services to workers in small scale industries in a district of Sri Lanka Methods A cross-sectional study was conducted among workers in selected small scale industries in Gampaha district in Sri Lanka. A small scale industry was defined as a work setting with less than 20 workers. The study population consisted of workers in four selected small scale industry categories namely food and beverages, apparel, non metallic mineral products and fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Previous research has highlighted the challenges in enhancing the occupational safety of workers in low‐ and middle‐income countries, particularly in informal sectors . In these sectors, including mining, welding, printing, textile manufacturing, and other small industries, substantial gaps exist in prevention practice use and preventative behavior . Our findings are consistent with these studies, showing that just under half of the surveyed agate workers in Khambhat used prevention practices.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has highlighted the challenges in enhancing the occupational safety of workers in low‐ and middle‐income countries, particularly in informal sectors . In these sectors, including mining, welding, printing, textile manufacturing, and other small industries, substantial gaps exist in prevention practice use and preventative behavior . Our findings are consistent with these studies, showing that just under half of the surveyed agate workers in Khambhat used prevention practices.…”
Section: Discussionsupporting
confidence: 88%
“…About one million workers die every year from occupational exposure to ambient air contaminated with dust, carcinogenic, and pathogenic particles [5]. The health effects from dust particles are dependent upon their size distribution and chemical constituents [6]. A study has revealed that "outdoor workers in Almaty during the cold season are at high risk of respiratory diseases."…”
Section: Introductionmentioning
confidence: 99%